SAC lead-free soldering lug and preparation method thereof

By adding micro-nano copper powder and Ag3Sn nanoparticles to the SAC-based lead-free soldering sheets, the Cu@Sn core-shell structure and Cu6Sn5 weld structure are formed, which solves the problems of insufficient reliability and poor mechanical properties of the solder joints of traditional lead-free solder joints, and has achieved significant improvements in the reliability and mechanical properties of the solder joints.

CN119566616APending Publication Date: 2025-03-07EUNOW ELECTRONICS TECH CO LTD SUZHOU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411680869.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional lead-free soldering sheets are difficult to meet market demand due to insufficient reliability of solder joints, excessive melting point and high cost. In particular, the poor wetting properties of SAC-based lead-free soldering sheets and the high Ag content lead to the formation of brittle Ag3Sn phase, which affects the mechanical properties of the solder joints and the reliability of the solder joints.

Method used

By adding micro-nano copper powder and Ag3Sn nanoparticles to the SAC-based lead-free soldering sheet, Cu@Sn core-shell structure and Cu6Sn5 weld structure are formed, the reliability of the solder joints is improved, and the mechanical properties of the solder sheet are improved through the refinement and dispersion strengthening of Ag3Sn nanoparticles.

Benefits of technology

It significantly improves the reliability of the solder joints and the mechanical properties of the solder sheet, improves the distribution uniformity and deformation resistance of the solder joints, and meets the needs of improving high temperature stability and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119566616A_ABST
    Figure CN119566616A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lead-free soldering lugs, and particularly discloses an SAC-series lead-free soldering lug and a preparation method thereof. The SAC series lead-free soldering lug is prepared from the following raw materials in parts by mass: 20 to 40 parts of SAC305, 60 to 80 parts of micro-nano copper powder and 1 to 5 parts of Ag3Sn nanoparticles. According to the SAC-series lead-free soldering lug, the micro-nano copper powder and the Ag3Sn nanoparticles are added, and under the synergistic effect of the micro-nano copper powder and the Ag3Sn nanoparticles, the reliability of welding spots and the mechanical performance of the soldering lug are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of soldering sheets, and more specifically, to a SAC series lead-free soldering sheet and a preparation method thereof. Background Art

[0002] With the rapid development of the electronics industry, the new generation of electronic products has put forward higher requirements in terms of functional diversity and reliability, which has also brought more stringent challenges to the existing electronic packaging technology. Advanced and mature electronic packaging technology can not only effectively guarantee the long-term stable operation of electronic components, but also improve the working limit of products on the basis of ensuring system stability. Therefore, lead-free solder sheets, as a key component of electronic packaging technology, have gradually received attention in recent years.

[0003] However, traditional lead-free solder sheets are difficult to meet market demand due to problems such as insufficient solder joint reliability, high melting point and high cost. Therefore, it is of great significance to develop new lead-free solder sheets. At present, SAC (Sn-Ag-Cu) lead-free solder sheets have very excellent mechanical properties and still have very good stability at high temperatures. However, compared with traditional SnPd solder, the wettability of SAC lead-free solder sheets is relatively poor. In addition, the high Ag content of SAC lead-free solder sheets will lead to the formation of brittle Ag3Sn phase, which will have an adverse effect on the mechanical properties of the solder sheet alloy and reduce the reliability of the solder joints of SAC lead-free solder sheets.

[0004] Therefore, developing a SAC-based lead-free solder sheet with high solder joint reliability and good mechanical properties is of great significance to the development of lead-free solder sheets. Summary of the invention

[0005] In order to improve the reliability and mechanical properties of solder joints of SAC series lead-free solder sheets, the present application provides a SAC series lead-free solder sheet and a preparation method thereof.

[0006] In a first aspect, the present application provides a SAC-based lead-free solder sheet, which adopts the following technical solution: A lead-free solder sheet of SAC series is made of the following raw materials in parts by mass: 20-40 parts of SAC305, 60-80 parts of micro-nano copper powder, and 1-5 parts of Ag3Sn nano particles.

[0007] By adopting the above technical solution, during the welding process, SAC305 provides Sn source, and micro-nano copper powder provides Cu source. Tin melts while copper does not melt. Tin becomes liquid metal to coat copper particles, forming metal powder with Cu@Sn core-shell structure. During the remelting process, the outer Sn of the core-shell structure particles reacts with the Cu in the core to form intermetallic compounds to achieve the purpose of metallurgical bonding. Moreover, the intermetallic compounds on the outer layers of these particles diffuse and cross-link to form a uniform mesh weld, while the internal Cu core is retained, thereby forming a structure in which a layer of Cu6Sn5 weld is interspersed with tiny single copper particles, thereby improving the reliability of the solder joint.

[0008] The Cu6Sn5 particles and nano-Ag3Sn particles formed above refine the secondary Ag3Sn and Cu6Sn5 IMC phases in the solder sheet matrix, promote dispersion strengthening, inhibit the propagation of force in the solder sheet matrix, produce better deformation resistance, and improve the mechanical properties of the solder sheet.

[0009] In summary, the SAC lead-free solder sheet of the present application improves the solder joint reliability and the mechanical properties of the solder sheet by adding micro-nano copper powder and Ag3Sn nanoparticles under the synergistic effect of the two.

[0010] In a specific embodiment, the method for preparing the Ag3Sn nanoparticles comprises the following steps: (1) adding stannous chloride dihydrate, silver nitrate and 1,10-phenanthroline to anhydrous methanol in sequence and mixing them uniformly to obtain a solution A; (2) dissolving a reducing agent and a dispersing agent in an aqueous ammonia solution to obtain an alkaline solution B; (3) dropping alkaline solution B into solution A, reacting by ultrasonication at 30-50°C for 20-30 min, separating the solid and the liquid, washing the solid with ethanol, vacuum drying, and grinding to obtain Ag3Sn nanoparticles.

[0011] By adopting the above technical scheme, Ag and Sn are first prepared by reduction reaction, and then Ag and Sn react to generate Ag3Sn through dispersion and coordination under the action of 1,10-phenanthroline. The preparation method is simple, that is, Ag3Sn nanoparticles can be prepared by simple raw materials and equipment, which is suitable for large-scale industrial production and has good applicability.

[0012] In a specific embodiment, in the step (1), the molar ratio of stannous chloride dihydrate to silver nitrate is 1:3, the concentration of silver nitrate in solution A is 0.015-0.06 mol / L, and the solid-liquid ratio of 1,10-phenanthroline to anhydrous methanol is 2.7-3.1:100 in g:ml; In the step (2), the ammonia solution is 5.0-5.6 wt %, and the solid-liquid ratio of the reducing agent to the ammonia solution is 3-9:100.

[0013] By adopting the above technical solution and controlling the concentration of the reaction solution, a mixture containing different nanoparticles can be generated to obtain a pure Ag3Sn nanoparticle compound.

[0014] In a specific embodiment, in step (2), the reducing agent is sodium borohydride, and the dispersing agent is polyethylene glycol; the mass ratio of sodium borohydride to polyethylene glycol is (3-9):(1-5).

[0015] By adopting the above technical scheme, sodium borohydride has the advantages of mild reaction conditions, few side reactions and high yield; polyethylene glycol contains two hydrophilic groups, hydroxyl and ether bonds, and no hydrophobic group, and its water solubility and stability are extremely good, and it is not easily affected by electrolytes, acids and alkalis, so that it is serpentine in aqueous solution, and it is very easy to form strong hydrogen bonds with the surface of reduced metal single particles, and its ether bonds are also very easy to have affinity with the single particles, so that polyethylene glycol can be easily adsorbed on the surface of the particles to form a layer of polymer film to wrap the metal single particles, and its molecular bonds are serpentine and extend into the aqueous solution, so that the protective film wrapped on the surface of the particles has a certain thickness. When colloidal particles with the same charge approach each other, the electrostatic repulsion plus the steric hindrance of the polymer greatly weaken the attraction between the single particles, thereby effectively preventing the growth of particles, inhibiting the agglomeration of particles, playing a good dispersion role, and being beneficial to the combination of Ag single substance and Sn single substance.

[0016] In a specific embodiment, in step (3), the dropping speed of the alkaline solution B is 0.05-0.1 ml / L.

[0017] By adopting the above technical scheme, when the rate of adding solution B is too fast, a large amount of reducing agent is introduced in a short time, and the reaction rate is too fast, resulting in larger particle size of the generated Ag and Sn single substances; on the contrary, when the rate of adding solution B is too slow, the reaction rate is reduced, and the reducing agent is consumed after the Ag and Sn single substances are generated, and their crystal nuclei are dispersed in the entire solution before they have time to grow, reducing the possibility of crystal nuclei growth.

[0018] In a specific implementation manner, the mass ratio of the SAC305 to the micro-nano copper powder is (2-3): (7-8).

[0019] By adopting the above technical solution, the mass ratio between SAC305 and micro copper powder is optimized, so that the coating property of Sn on Cu is better; at the same time, during the remelting process, the distribution uniformity of the formed Cu6Sn5 in the solder joint is better, which further improves the reliability and mechanical properties of the solder joint.

[0020] In a specific embodiment, the average particle size of the micro-nano copper powder is 50 nm-7 μm, and more preferably 1 μm.

[0021] By adopting the above technical solution, when the copper powder particle size is small, severe oxidation will occur and no effective solder joint can be formed; when the copper powder particle size is large, the reaction rate will decrease, and the amount of Cu6Sn5 generated in a shorter heating time will decrease, which is not conducive to the formation of a network structure; at the same time, copper powder with a larger particle size is not conducive to lowering the melting point of the solder sheet during welding, lowering the welding temperature, and reducing the impact on the parent material and substrate during the welding process.

[0022] In a specific embodiment, the micro-nano copper powder is obtained after pickling pretreatment, and the pickling pretreatment specifically includes the following steps: Wash the micro-nano copper powder with 5wt% dilute hydrochloric acid, then wash with anhydrous ethanol, and dry; The pickled micro-nano copper powder was immersed in a 5wt% formic acid solution, subjected to ultrasonic treatment for 5 minutes, washed and dried to obtain modified micro-nano copper powder.

[0023] By adopting the above technical scheme, pickling with dilute hydrochloric acid can remove the oxide layer on the surface of the micro-nano copper powder, and then through formic acid treatment, the oxide skin on the surface of the micro-nano copper powder is completely removed and a reduction layer is generated on the surface, which can reduce the oxidation of the copper powder during the welding process, reduce the possibility of effectively forming solder joints due to oxidation of the copper powder, and can effectively ensure the reliability and quality of the solder joints.

[0024] In the second aspect, the present application provides a method for preparing a SAC-based lead-free solder sheet, adopting the following technical solution: A method for preparing a SAC-based lead-free solder sheet: according to the ratio, tin alloy powder, micro-nano copper powder and Ag3Sn nanoparticles are stirred and mixed, put into a tablet press mold, and maintained at a pressure of 20Mpa for 2 minutes.

[0025] By adopting the above technical solution, compared with traditional soldering sheets, the soldering sheet prepared in the present application has the characteristics of low-temperature preparation and high-temperature service. By applying external pressure, close contact between the components in the soldering sheet is promoted, and the reaction is more rapid, which makes the final weld have less pore content; at the same time, it also makes the IMC distribution more extensive, which can be applied to electronic packaging technology to ensure the long-term normal operation of electronic components.

[0026] In summary, this application has the following beneficial effects: 1. The SAC lead-free solder sheet of the present application improves the reliability of solder joints and the mechanical properties of solder sheets by adding micro-nano copper powder and Ag3Sn nanoparticles under the synergistic effect of the two; 2. The present application controls the mass ratio of micro-nano copper powder to SAC305 to make the coating of Sn on Cu better; at the same time, during the remelting process, the distribution uniformity of the formed Cu6Sn5 at the solder joint is better, which further improves the reliability and mechanical strength of the solder joint; 3. The present application controls the average particle size of micro-nano copper powder. Copper powder with appropriate particle size can increase the reaction rate of copper, increase the number of IMC generated in a shorter heating time, and is conducive to the formation of a network structure. At the same time, copper powder with appropriate particle size can effectively reduce the melting point of the solder sheet during welding, reduce the welding temperature, and reduce the impact on the parent material and substrate during the welding process; 4. When preparing the SAC series lead-free solder sheet of the present application, external pressure is applied to promote close contact between the components in the solder sheet, and the reaction is faster, which makes the final weld less pore content; at the same time, it also makes the IMC distribution more extensive, which can be applied to electronic packaging technology to ensure the long-term normal operation of electronic components. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a solder joint morphology image of the SAC series lead-free solder sheet after soldering prepared in Example 1 of the present application; Figure 2 This is a solder joint morphology image of the SAC series lead-free solder sheet after soldering prepared in Example 2 of the present application; Figure 3 This is a solder joint morphology image of the SAC series lead-free solder sheet after soldering prepared in Comparative Example 1 of the present application; Figure 4 This is a solder joint morphology image of the SAC series lead-free solder sheet after soldering prepared in comparative example 3 of the present application. DETAILED DESCRIPTION

[0028] The following are examples and attached Figure 1-4 This application is described in further detail.

[0029] Preparation Example Preparation Example 1 This preparation example provides a Ag3Sn nanoparticle, and the preparation method is as follows: 1. Dissolve 2.26 g of stannous chloride dihydrate, 5.1 g of silver nitrate and 2.9 g of 1,10-phenanthroline in 100 ml of anhydrous methanol and mix well to obtain solution A; 2. Dissolve 6 g of sodium borohydride and 3 g of polyethylene glycol in 100 ml of 5.3 wt% ammonia water at 20°C, stir at 200 rpm, completely dissolve, and mix evenly to form solution B; 3. Add solution B drop by drop into solution A at a dropping speed of 0.08 ml / s, react ultrasonically at 40°C for 25 min, let stand for 2 h, separate the solid and liquid, wash the solid with ethanol, vacuum dry, and grind to obtain Ag3Sn nanoparticles.

[0030] Preparation Example 2 This preparation example provides a Ag3Sn nanoparticle, and the preparation method is as follows: 1. Dissolve 1.13 g of stannous chloride dihydrate, 2.55 g of silver nitrate and 2.7 g of 1,10-phenanthroline in 100 ml of anhydrous methanol and mix well to obtain solution A; 2. Dissolve 3 g of sodium borohydride and 1 g of polyethylene glycol in 100 ml of 5.0 wt% ammonia water at 20°C, stir at 200 rpm, completely dissolve, and mix evenly to form solution B; 3. Add solution B drop by drop into solution A at a dropping speed of 0.05 ml / s, react ultrasonically at 30°C for 20 min, let stand for 2 h, separate the solid and liquid, wash the solid with ethanol, vacuum dry, and grind to obtain Ag3Sn nanoparticles.

[0031] Preparation Example 3 This preparation example provides a Ag3Sn nanoparticle, and the preparation method is as follows: 1. Dissolve 4.52 g of stannous chloride dihydrate, 10.2 g of silver nitrate and 3.1 g of 1,10-phenanthroline in 100 ml of anhydrous methanol and mix well to obtain solution A; 2. Dissolve 9 g of sodium borohydride and 5 g of polyethylene glycol in 100 ml of 5.6 wt% ammonia water at 20°C, stir at 200 rpm, completely dissolve, and mix evenly to form solution B; 3. Add solution B drop by drop into solution A at a dropping speed of 0.1 ml / s and react ultrasonically at 40°C for 30 min. Let stand for 2 h, separate the solid and liquid, wash the solid with ethanol, vacuum dry, and grind to obtain Ag3Sn nanoparticles. Example

[0032] Example 1 This embodiment discloses a SAC-based lead-free solder sheet, including the following raw material components: 30g SAC305, 70g micro-nano copper powder, and 3g Ag3Sn nanoparticles.

[0033] In this embodiment, SAC305 is Sn96.5Ag3.0Cu0.5 powder with an average particle size of 20 μm; the micro-nano copper powder is 99.99% copper powder with an average particle size of 1 μm; and the Ag3Sn nanoparticles are obtained in Preparation Example 1.

[0034] The preparation method of SAC lead-free solder sheet is as follows: Take micro-nano copper powder with an average particle size of 1 μm, wash it with 5wt% dilute hydrochloric acid to remove the surface oxide layer, then wash it with anhydrous ethanol, and dry it to obtain pretreated micro-nano copper powder; The pretreated micro-nano copper powder was immersed in a 5wt% formic acid solution, ultrasonically treated for 5 minutes, then washed with anhydrous ethanol and dried to obtain modified micro-nano copper powder.

[0035] 30g SAC305, 70g modified micro-nano copper powder and 3g Ag3Sn nanoparticles were fully mixed and then put into a tablet press mold, kept at a pressure of 20Mpa for 2 minutes and then taken out. Finally, the prepared solder sheet was stored at a temperature of 20°C in a ventilated and light-shielded environment to obtain a SAC series lead-free solder sheet.

[0036] After sandpaper polishing, remove the oxide film with dilute hydrochloric acid, wash with anhydrous ethanol and dry. Place the obtained solder sheet between two copper plates in an appropriate amount, put it into a vacuum furnace and solder it at 240℃ for 10 minutes, and then cool it to room temperature with the furnace. Observe the solder joint morphology, it can be seen that the IMC of the solder joint is evenly distributed and continuous in a mesh shape, and the distribution is dense, such as Figure 1 shown.

[0037] Example 2 The only difference between this embodiment and embodiment 1 is that the SAC-based lead-free solder sheet includes the following raw material components: 20 g SAC305, 80 g micro-nano copper powder, and 3 g Ag3Sn nanoparticles.

[0038] After sandpaper polishing, remove the oxide film with dilute hydrochloric acid, wash with anhydrous ethanol, and dry. Place the obtained solder sheet between two copper plates in an appropriate amount, put it into a vacuum furnace, solder it at 240℃ for 10 minutes, and then cool it to room temperature with the furnace. Observe the solder joint morphology, it can be seen that the IMC of the solder joint is evenly distributed and continuous in a mesh shape, and the distribution is relatively dense, such as Figure 2 shown.

[0039] Example 3 The only difference between this embodiment and embodiment 1 is that the SAC-based lead-free solder sheet includes the following raw material components: 40 g SAC305, 60 g micro-nano copper powder, and 3 g Ag3Sn nanoparticles.

[0040] Example 4 The only difference between this embodiment and embodiment 1 is that the Ag3Sn nanoparticles are obtained according to preparation example 2.

[0041] Example 5 The only difference between this embodiment and embodiment 1 is that the Ag3Sn nanoparticles are obtained according to preparation example 3.

[0042] Example 6 The only difference between this embodiment and embodiment 1 is that the SAC-based lead-free solder sheet includes the following raw material components: 30 g SAC305, 70 g micro-nano copper powder, and 1 g Ag3Sn nanoparticles.

[0043] Example 7 The only difference between this embodiment and embodiment 1 is that the SAC-based lead-free solder sheet includes the following raw material components: 30 g SAC305, 70 g micro-nano copper powder, and 5 g Ag3Sn nanoparticles.

[0044] Example 8 The only difference between this embodiment and embodiment 1 is that the micro-nano copper powder is 99.99% copper powder and has an average particle size of 50 nm.

[0045] Example 9 The only difference between this embodiment and embodiment 1 is that the micro-nano copper powder is 99.99% copper powder and has an average particle size of 7 μm.

[0046] Comparative Example Comparative Example 1 The difference between this comparative example and Example 3 is that the SAC in this comparative example is a lead-free solder sheet, comprising the following raw material components: 40 g SAC305, 60 g micro-nano copper powder.

[0047] In this comparative example, SAC305 is Sn96.5Ag3.0Cu0.5 powder with an average particle size of 20 μm; the micro-nano copper powder is 99.99% copper powder with an average particle size of 1 μm.

[0048] The preparation method of SAC lead-free solder sheet is as follows: Take micro-nano copper powder with an average particle size of 1 μm, wash it with 5wt% dilute hydrochloric acid to remove the surface oxide layer, then wash it with anhydrous ethanol, and dry it to obtain pretreated micro-nano copper powder; The pretreated micro-nano copper powder was immersed in a 5wt% formic acid solution, ultrasonically treated for 5 minutes, then washed with anhydrous ethanol and dried to obtain modified micro-nano copper powder.

[0049] 40g SAC305 and 60g modified micro-nano copper powder were fully stirred and then put into a tablet press mold, kept at a pressure of 20Mpa for 2 minutes and then taken out. Finally, the prepared solder sheet was stored at a temperature of 20°C in a ventilated and light-shielded environment to obtain a SAC series lead-free solder sheet.

[0050] After sandpaper polishing, remove the oxide film with dilute hydrochloric acid, wash with anhydrous ethanol and dry. Place the obtained solder piece between two copper plates in an appropriate amount, put it into a vacuum furnace and solder it at 240℃ for 10 minutes, and then cool it to room temperature with the furnace. Observe the solder joint morphology, it can be seen that the IMC distribution of the solder joint is uneven and element segregation occurs, such as Figure 3 shown.

[0051] Comparative Example 2 The only difference between this comparative example and Example 3 is that the SAC solder sheet in this comparative example is lead-free, and includes the following raw material components: 100 g SAC305 and 3 g Ag3Sn nanoparticles.

[0052] In this comparative example, SAC305 is Sn96.5Ag3.0Cu0.5 powder with an average particle size of 20 μm.

[0053] The preparation method of SAC lead-free solder sheet is as follows: 100g SAC305 and 3g Ag3Sn nanoparticles were fully stirred and then put into a tablet press mold, kept at a pressure of 20Mpa for 2 minutes and then taken out. Finally, the prepared solder sheet was stored at a temperature of 20°C in a ventilated and light-shielded environment to obtain a SAC series lead-free solder sheet.

[0054] Comparative Example 3 The only difference between this comparative example and Example 1 is that the SAC solder sheet in this comparative example is lead-free, and includes the following raw material components: 50g SAC305, 50g micro-nano copper powder, and 3g Ag3Sn nanoparticles.

[0055] In this comparative example, SAC305 is Sn96.5Ag3.0Cu0.5 powder with an average particle size of 20 μm; the micro-nano copper powder is 99.99% copper powder with an average particle size of 1 μm; and the Ag3Sn nanoparticles are obtained in Preparation Example 1.

[0056] The preparation method of SAC lead-free solder sheet is as follows: Take micro-nano copper powder with an average particle size of 1 μm, wash it with 5wt% dilute hydrochloric acid to remove the surface oxide layer, then wash it with anhydrous ethanol, and dry it to obtain pretreated micro-nano copper powder; The pretreated micro-nano copper powder was immersed in a 5wt% formic acid solution, ultrasonically treated for 5 minutes, then washed with anhydrous ethanol and dried to obtain modified micro-nano copper powder.

[0057] 50g SAC305, 50g modified micro-nano copper powder and 3g Ag3Sn nanoparticles were fully mixed and then put into a tablet press mold, kept at a pressure of 20Mpa for 2 minutes and then taken out. Finally, the prepared solder sheet was stored at a temperature of 20°C in a ventilated and light-shielded environment to obtain a SAC series lead-free solder sheet.

[0058] After sandpaper polishing, remove the oxide film with dilute hydrochloric acid, wash with anhydrous ethanol and dry. Place the obtained solder piece between two copper plates in an appropriate amount, put it into a vacuum furnace and solder it at 240℃ for 10 minutes, and then cool it to room temperature with the furnace. Observe the solder joint morphology, it can be seen that the IMC distribution of the solder joint is uneven and element segregation occurs, but the segregation is good, such as Figure 4 shown.

[0059] Performance Testing 1. Wettability test A certain amount of the SAC lead-free solder sheets prepared in the embodiments and comparative examples were cut and placed between two copper substrates (40 mm × 40 mm × 0.2 mm) cleaned with acetone and alcohol. The samples were then placed on a heated plate to obtain spread samples. The wetting area was measured using Image software. The test results are shown in Table 1.

[0060] 2. Tensile strength test The copper rod was ultrasonically cleaned with acetone and anhydrous ethanol in turn to remove the oxide layer and dirt on the surface of the copper rod, and then the end face (5mm×5mm) was polished for standby use; the two copper rods were placed on the high-temperature glass in a straight line, and the spacing between the two copper rods was controlled to be 0.5mm. The flux was applied between the two copper rods, and they were placed on the heating platform. The SAC series lead-free solder sheets prepared in the embodiment and the comparative example were respectively added between the two copper rods for welding to obtain solder joints; the four sides of the solder joints were polished with 800 mesh, 1200 mesh and 2000 mesh sandpaper, and the tensile strength was measured with a tensile strength tester after marking. The test results are shown in Table 1.

[0061] Table 1 Performance test data of Examples 1-9 and Comparative Examples 1-3 Combining Examples 1-9 and Comparative Examples 1-2 and Table 1, it can be seen that during the welding process, SAC305 provides Sn source, micro-nano copper powder provides Cu source, tin melts but copper does not melt, and the tin component liquid metal coats the copper particles to form a metal powder with a Cu@Sn core-shell structure. During the remelting process, the outer Sn of the core-shell structure particles reacts with the Cu in the core to form intermetallic compounds to achieve the purpose of metallurgical bonding, and the intermetallic compounds on the outer layers of these particles diffuse and cross-link to form a uniform mesh weld, while the internal Cu core is retained, thereby forming a layer of Cu6Sn5 weld with tiny single copper particles, which improves the reliability of the solder joint. The formed Cu6Sn5 particles and nano-Ag3Sn particles refine the secondary Ag3Sn and Cu6Sn5 IMC phases in the solder sheet matrix, promote dispersion strengthening, inhibit the propagation of force in the solder sheet matrix, produce better anti-deformation performance, and improve the mechanical properties of the solder sheet. Therefore, the SAC lead-free solder sheet of the present application improves the reliability of solder joints and the mechanical properties of the solder sheet by adding micro-nano copper powder and Ag3Sn nanoparticles under the synergistic effect of the two.

[0062] It can be seen from Examples 1-3 and Comparative Example 3 and Table 1 that the present application optimizes the mass ratio between SAC305 and micro-copper powder to achieve better Sn coating of Cu; at the same time, during the remelting process, the formed Cu6Sn5 has better distribution uniformity at the solder joints, further improving the reliability and mechanical properties of the solder joints.

[0063] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A SAC lead-free solder sheet, characterized in that: The invention is made of the following raw materials in parts by weight: 20-40 parts of SAC305, 60-80 parts of micro-nano copper powder and 1-5 parts of Ag3Sn nano particles.

2. The SAC lead-free solder sheet according to claim 1, characterized in that: The preparation method of the Ag3Sn nanoparticles comprises the following steps: Add stannous chloride dihydrate, silver nitrate and 1,10-phenanthroline to anhydrous methanol in sequence, and mix well to obtain solution A; Dissolving a reducing agent and a dispersant in an aqueous ammonia solution to obtain an alkaline solution B; The alkaline solution B is dropped into the solution A, and the solution is ultrasonically reacted at 30-50°C for 20-30 minutes. The solid and liquid are separated, and the solid is washed with ethanol, vacuum dried, and ground to obtain Ag3Sn nanoparticles.

3. The SAC lead-free solder sheet according to claim 2, characterized in that: In the step (1), the molar ratio of stannous chloride dihydrate to silver nitrate is 1:3, the concentration of silver nitrate in solution A is 0.015-0.06 mol / L, and the solid-liquid ratio of 1,10-phenanthroline to anhydrous methanol is 2.7-3.1:100 in g:ml; In the step (2), the ammonia solution is 5.0-5.6 wt %, and the solid-liquid ratio of the reducing agent to the ammonia solution is 3-9:

100.

4. The SAC lead-free solder sheet according to claim 2, characterized in that: In the step (2), the reducing agent is sodium borohydride, and the dispersing agent is polyethylene glycol; the mass ratio of the sodium borohydride to the polyethylene glycol is (3-9): (1-5).

5. The SAC lead-free solder sheet according to claim 2, characterized in that: In the step (3), the dropping speed of the alkaline solution B is 0.05-0.1 ml / L.

6. The SAC lead-free solder sheet according to claim 1, characterized in that: The mass ratio of the SAC305 to the micro-nano copper powder is (2-3): (7-8).

7. The SAC lead-free solder sheet according to claim 1, characterized in that: The average particle size of the micro-nano copper powder is 50nm-7μm.

8. The SAC lead-free solder sheet according to claim 7, characterized in that: The micro-nano copper powder is obtained after pickling pretreatment, and the pickling pretreatment specifically includes the following steps: The micro-nano copper powder was washed with 5wt% dilute hydrochloric acid, then washed with anhydrous ethanol, and dried; The pickled micro-nano copper powder was immersed in a 5wt% formic acid solution, ultrasonically treated for 5 minutes, washed and dried to obtain modified micro-nano copper powder.

9. A method for preparing a SAC lead-free solder sheet according to any one of claims 1 to 8, characterized in that: According to the ratio, tin alloy powder, micro-nano copper powder and Ag3Sn nanoparticles are stirred and mixed, put into a tablet press mold, and maintained at a pressure of 20Mpa for 2 minutes.